\[\boxed{\text{356\ (356).\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[y = 2x^{2} - 3x + 6;\ \ \ y = x + 12\]
\[- 2x^{2} - 3x + 6 = x + 12\]
\[2x^{2} - 4x - 6 = 0\ \ |\ :2\]
\[x^{2} - 2x - 3 = 0\]
\[x_{1} + x_{2} = 2,\ \ x_{1}x_{2} = - 3,\ \ \]
\[x_{1} = - 1,\ \ x_{2} = 3.\]
\[x = - 1 \rightarrow \ \ y = 11\]
\[x = 3 \rightarrow \ y = 15.\]
\[Ответ:( - 1;11),\ (3;15).\]
\[\boxed{\text{356.}\text{\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
Пояснение.
Решение.
\[1)\ f(x) = 0,2x + 3\]
\[0,2x + 3 = 0\]
\[0,2x = - 3\]
\[x = - 15.\]
\[Ответ:x = - 15.\]
\[2)\ g(x) = 35 - 2x - x^{2}\]
\[x^{2} + 2x - 35 = 0\]
\[x_{1} + x_{2} = - 2,\ \ x_{1} = - 7\]
\[x_{1}x_{2} = - 35,\ \ x_{2} = 5.\]
\[Ответ:x = - 7;\ \ x = 5.\]
\[3)\ \varphi(x) = \sqrt{x + 3}\]
\[\sqrt{x + 3} = 0\]
\[x + 3 = 0\]
\[x = - 3.\]
\[Ответ:x = - 3.\]
\[4)\ h(x) = \frac{x^{2} - x - 6}{x + 3};\ \ x \neq - 3\]
\[x^{2} - x - 6 = 0\]
\[x_{1} + x_{2} = 1,\ \ x_{1} = 3\]
\[x_{1}x_{2} = - 6,\ \ x_{2} = - 2\]
\[Ответ:x = - 2;\ \ x = 3.\]
\[5)\ f(x) = x^{3} - 4x\]
\[x^{3} - 4x = 0\]
\[x \cdot \left( x^{2} - 4 \right) = 0\]
\[x = 0;\]
\[x = \pm 2.\]
\[Ответ:x = \pm 2;x = 0.\]
\[6)\ f(x) = x^{2} + 1\]
\[x^{2} + 1 = 0\]
\[x^{2} = - 1\]
\[нулей\ функции\ нет.\ \]
\[Ответ:нет\ нулей\ функции.\]